Recommendations for policies supporting vulnerable groups in transitioning to a green economy in Vietnam - Le Hoang Lan (Journal of State Management, 2024)
Vietnam is one of the pioneering countries in the world in green transition. In any transition process, vulnerable groups face difficulties adapting to new changes. This article analyzes and evaluates the current situation of constructing and implementing support policies for vulnerable groups in the transition to a green economy in Vietnam while also proposing some solutions to improve support policies for this group.